Economic growth and under-five malaria mortality in Tanzania mainland: from correlation analysis to causality - Byaro, Mwoya; Kinyondo, Abeli; Musonda, Patrick (International Journal of Health, 2017)
This paper establishes empirical evidence related with correlation and causality between economic growth (as measured by GDP per capita) and under-five malaria mortality in Tanzania Mainland. The goal is to contribute knowledge on the existing relationship between economic growth and under-five malaria mortality. Correlation and scatter regression analysis plot were employed to find out the relationship among the (GDP per Capita), Insecticides Treated Nets (ITNs) distributed, Human Resources (physicians and nurses) and under-five malaria mortality from the year 2004 to 2015. Moreover, Granger Causality test was applied to test the causal link between the economic growth and under-five malaria Mortality. The economic growth (as measured by GDP per Capita) and number of ITNs distributed under various malaria campaigns have significant unidirectional causality to under-five malaria mortality while there is no causality evidence between human resource for health (physicians and nurses) and under-five malaria mortality despite the observed correlation relationship. Since economic growth and ITNs have unidirectional causal link with under-five malaria mortality, it implies that any changes in GDP per Capita and ITNs will change under-five malaria mortality. The researchers and policy makers need to gather more evidence on ITNs and economic growth to assess the risk of under-five malaria mortality to inform decision making.